1997
DOI: 10.1002/(sici)1099-081x(199707)18:5<459::aid-bdd31>3.3.co;2-7
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Coffee With Milk and Tea With Milk on the Bioavailability of Tetracycline

Abstract: The eect of milk added to coee or black tea on the bioavailability of tetracycline was evaluated in 12 healthy volunteers according to a crossover design. Results showed that even a small volume of milk containing extremely small amounts of calcium severely impair the absorption of the drug, so that the presence of this metal ion should be carefully controlled in order to avoid decreasing the available tetracycline. &1997 by John Wiley & Sons, Ltd.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2005
2005
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 4 publications
0
4
0
Order By: Relevance
“…[7][8][9][10][11][12][13][14][15][16] In the present study, it was confirmed that the amount of calcium contained in the Kampo preparation investigated in this study are much higher than that of 1082 Vol. 32, No.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[7][8][9][10][11][12][13][14][15][16] In the present study, it was confirmed that the amount of calcium contained in the Kampo preparation investigated in this study are much higher than that of 1082 Vol. 32, No.…”
Section: Discussionmentioning
confidence: 99%
“…Jung et al 15) have reported that almost the same amount of calcium (37.5 mg) as the present study reduces the bioavailability of tetracycline (250 mg) by approximately 50%, which supports the results of the present study.…”
Section: Discussionmentioning
confidence: 99%
“…As most antacids contain aluminum or magnesium hydroxide and/or calcium carbonate ions, such coadministration have reduced greatly the bioavailability of the antibiotic. However, complexation can also arise due to the calcium ions present in milk and other dairy products (Jung et al 1997). For example, for democycline, only 13% was absorbed when administered with milk.…”
Section: Drug Complexationmentioning
confidence: 89%
“…For example, tetracycline should not be taken with milk as this can significantly reduce the absorption; even the small amounts added to tea or coffee can have a clinically important effect (6) . For this reason, many patients alter their usual food intake to comply with dosing guidelines and may reduce their overall intake.…”
Section: Food Avoidancementioning
confidence: 99%